Effects of aromatherapy on sleep quality in patients: Protocol for an umbrella review - Hongrui Shi; Mengqi Liu; Xinxin Fan; Wei Peng; Yan Hu (PLoS ONE, 2025)
Introduction Poor sleep quality affects disease recovery and overall quality of life. Aromatherapy has been shown to improve sleep quality by alleviating anxiety, promoting relaxation, and enhancing blood circulation. Several meta-analyses have reported the effects of aromatherapy on sleep quality, however, the efficacy varies widely, with some studies showing that the effects are negligible or inconsistent. A comprehensive review synthesizing the available evidence on the impact of aromatherapy on sleep quality is still needed. Therefore, this study aims to provide an umbrella review summarizing all available systematic reviews and meta-analyses investigating the effects of aromatherapy on sleep quality. Methods and analysis A thorough literature search will be conducted across six English-language databases and four Chinese-language databases, following the Joanna Briggs Institute (JBI) methodology for umbrella reviews. Two reviewers will independently screen all articles to determine their eligibility based on pre-established inclusion criteria. Additionally, a manual search will be performed by reviewing the reference lists of the included studies. Data extraction will be conducted from all eligible studies, and the quality will be assessed using the Assessment of Multiple Systematic Reviews-2 (AMSTAR 2) tool. The study selection process will be presented using a PRISMA flow diagram. Statistical analyses will be performed using appropriate statistical methods to summarize and describe the findings. Results This study aims to provide comprehensive evidence by systematically evaluating the effects of aromatherapy on sleep quality in patients. It seeks to uncover the impact of aromatherapy on sleep quality across different patient populations and explore variations in its effectiveness based on disease type and the form of aromatherapy used. We will conduct a systematic evaluation of all eligible systematic reviews and meta-analyses. Subgroup analysis will also be performed, if applicable, to divide patients into groups according to how aromatherapy attributes (e.g., population type, dosage, route of administration) and disease types affect the effect size. PROSPERO registration number CRD42024580250.